PENGARUH PERSEPSI HARGA DAN KUALITAS PRODUK TERHADAP NIAT PEMBELIAN ULANG PADA PELANGGAN SURABAYA LEATHER - Ilham Munif Bahasuan; Krismi Budi Sienatra (Jurnal Performa)
This study aims to determine the effect of perceived price and product quality on repurchase intentions with the object under study is Surabaya Leather. The variables used in this study are the perception of price and product quality as independent variables and repurchase intention as the dependent variable. The method used is quantitative multiple linear regression. The sample used in this study used a non-probability sampling method with a census technique or a saturated sample and a sample of 40 respondents. Data collection techniques in this study were carried out by distributing questionnaires using a Likert scale of 1-5. Based on the results of data analysis, it can be concluded that the price perception variable has a partial and significant effect on repurchase intentions, as well as the product quality variable has a partial and significant effect on repurchase intentions. In addition to the model feasibility test, it can be found that the perception of price and product quality has a significant value simultaneously on repurchase intention.